Uji Kemampuan Anti Nyamuk Elektrik Serbuk Alang-Alang (Imperata Cylindrica) Terhadap Kematian Nyamuk - Rahman, Sartika Fathir; Yunicho, Yunicho; Sangaji, Sarimita A. (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
Mosquitoes are small and slender insects. The body consists of three separate parts, namely the head (caput), chest (thorax), and abdomen. Every year, hundreds of millions of cases of disease transmission to humans occur through insects. This poses a global public health challenge because it spreads widely and rapidly. It is known as arthropod-borne disease or